27‐5L: Late‐News Paper: Elongated Semiconductor Nanorods — Emitter of Polarized Light in Red and Green. Issue 1 (May 2016) - Niehaus, Jan; Jochum, Tobias; Weller, Horst
Abstract : Hereby we present high quality CdSe/CdS nanorodsemitting in red and green for optoelectronic devices. Beside high quantum yields a degree of polarization above 90% can be shown. The synthesis is based on the continuous flow technique allowing production in large amounts as well as the systematic variation of the parameters.